Intervenção com adolescentes vítimas de abuso sexual infantil - Kich, Priscila Viana (2014)
People who have experienced sexual abuse in their childhood or adolescence carry numerous emotional sequels from those abuses varying in degrees and may even become multipliers of maltreatments. The main subject of this study is to analyze a therapeutic group developed with seven teenage girls who have been sexually abused. It was an intervention aimed to decrease the consequences caused by sexual abuse and also aimed to improve the coping repertoire of the participants. The whole process had twelve sessions and was divided into phases, each containing its specific goals: I - Preparation - to lessen the sensitiveness to facilitate auto exposure; II - Revelation and discourse of feelings - to facilitate the revelation of sexual abuse and to promote exposure of their feelings;III - Acceptance - discuss the acceptance of sexual abuse and its place in the history of one's life;IV - Prevention - to facilitate the learning of selfprotective behaviors that prevent reoccurrence of the abuse.The descriptio n of the process was done in sessions containing: strategies used, report of the development, evaluation and discussion. The results show that the gradual group exposure could facilitate the report of sexual abuse by the victims and expression of their fee lings making a way for prevention of the reoccurrence by the learning of self-protection behaviors.